Solitons, bilinear Bäcklund transformations and conservation laws for a -dimensional Bogoyavlenskii-Kadontsev-Petviashili equation in a fluid, plasma or ferromagnetic thin film. Issue 7 (12th April 2017) - Yin, Hui-Min; Tian, Bo; Zhen, Hui-Ling; Chai, Jun; Liu, Lei; Sun, Yan
Abstract: In this paper, we investigate a( 2 + 1 ) -dimensional Bogoyavlenskii–Kadontsev–Petviashili equation in a fluid, plasma or ferromagnetic thin film. Through the Bell polynomials, Hirota method and symbolic computation, the one- and two-kink-soliton solutions are derived. Bäcklund transformation, Lax pair and conservation laws are presented. Elastic collisions including the oblique, parallel, unidirectional and bidirectional collisions between the two-kink solitons are discussed. In addition, the relation between the velocities and wave numbers of the two-kink solitons are analysed. When wave numbersb j > 0, ν j x, the velocities in the x axis, increase with wave numbersa j increasing. Withb j increasing, ν j x increase whena j 4 - 3 b j 2 > 0, while decrease whena j 4 - 3 b j 2 < 0 .ν j y, the velocities in the y axis, increase witha j increasing andb j decreasing.